Sites of recurrent disease and prognostic factors in SCLC patients treated with radiochemotherapy. (December 2017) - Bütof, Rebecca; Gumina, Calogero; Valentini, Chiara; Sommerer, Antje; Appold, Steffen; Zips, Daniel; Löck, Steffen; Baumann, Michael; Troost, Esther G.C.
Highlights: Most recurrences occurred within the primary tumor or initially affected lymph nodes. All sites of loco-regional recurrence had received 92–106% of the prescribed dose. No isolated nodal failure occurred, supporting the use of selective nodal irradiation. Abstract: Objectives: Concurrent radiochemotherapy (RCHT) is standard treatment in locally advanced small cell lung cancer (SCLC) patients. Due to conflicting results on elective nodal irradiation (ENI) or selective node irradiation (SNI) there is no clear evidence on optimal target volumes. Therefore, the purposes of this study were to assess the sites of recurrent disease in SCLC and to evaluate the feasibility of SNI versus ENI. Methods: A retrospective single-institution study of 43 consecutive patients treated with RCHT was performed. After state-of-the-art staging including FDG-PET/CT, all patients underwent three-dimensional conformal radiotherapy to a total dose of 45 Gy in twice-daily fractions of 1.5 Gy starting concurrently with the first or second chemotherapy cycle. All sites of loco-regional recurrences were correlated to the initial tumor and dose delivered. The impact of potential prognostic variables on outcome was evaluated using the Cox-regression model. Results: 13 patients (30%) relapsed locally or regionally: six within the initial primary tumor volume, five within the initially affected lymph nodes, one metachronously within primary tumor and initially affected lymph nodes, and one both inside and outside of the initial nodal disease. All sites of loco-regional recurrence had received 92–106% of the prescribed dose. Conclusion: In our study most recurrences occurred within the primary tumor or initially affected lymph nodes, or distantly. We did not register any case of isolated nodal failure, supporting the use of selective nodal irradiation, possibly with the addition of supraclavicular irradiation in patients with nodal disease in the upper mediastinum.